Informal economy and environmental degradation in developing countries: the conditioning role of institutional quality - Si, Chengyu; Hassan, Fatma Ahmed; Antohi, Valentin Marian; Ahmad, Waqar; Fortea, Costinela; Cristache, Nicoleta; Alshammari, Fuhaid; Zlati, Monica Laura (Frontiers in Environmental Science, 2025)
Environmental degradation, particularly through rising carbon dioxide (CO2) and greenhouse gas (GHG) emissions, is a pressing challenge for developing countries where large informal economies often escape regulatory oversight. This study investigates the impact of the informal economy on environmental degradation, tests for a potential nonlinear (U-shaped) relationship, and examines how this nexus is moderated by institutional quality. Using annual panel data for 120 developing countries over 2002–2020, we apply fixed effects and system GMM estimators with two measures of informal economy including Multiple Indicators Multiple Causes (MIMIC) model and the Dynamic General Equilibrium (DGE) model estimates, and four institutional indicators including control of corruption (COC), rule of law (ROL), regulatory quality (RQ), and government effectiveness (GE). The results reveal that the informal economy significantly intensifies CO2 and GHG emissions. Furthermore, the squared term of informal economy confirms a U-shaped relationship, suggesting that informality may initially reduce emissions at very low levels but exacerbates them once it surpasses a threshold. Moreover, the results indicate that higher institutional quality, as reflected in better COC, ROL, RQ, and GE, mitigates the adverse effects of the informal economy on CO2 and GHG emissions. This highlights a significant substitutability between the informal economy and institutional quality, indicating that improvements in institutions will not only reduce the informality but also weaken its harmful impact on environmental degradation. The findings suggest that policymakers should prioritize strengthening institutional frameworks, particularly in areas related to COC, ROL, RQ, and GE to mitigate the environmental harm caused by the informal economy. Effective institutional reforms can serve as a dual strategy to both formalize economic activities and improve environmental sustainability. Beyond generic governance reforms, subsidizing cleaner technologies for highly polluting informal sectors (such as brick kilns and leather tanning) and adopting incentive-based formalization programs can effectively curb emissions while safeguarding livelihoods.